Pomalidomide plus dexamethasone for patients with relapsed or refractory multiple myeloma: Final results of the non‐interventional study POSEIDON and comparison with the pivotal phase 3 clinical trials. (15th November 2021) - Dechow, Tobias; Aldaoud, Ali; Behlendorf, Timo; Knauf, Wolfgang; Eschenburg, Henning; Groschek, Matthias; Hansen, Richard; Söling, Ulrike; Grebhardt, Sina; Siebenbach, Hans Ulrich; Vannier, Corinne; Potthoff, Karin
Abstract: Background: Prognosis of patients with multiple myeloma (MM) who have relapsed on or become refractory to immunomodulators and bortezomib is poor, and treatment options are limited. While pomalidomide plus low‐dose dexamethasone (POM/DEX) has demonstrated efficacy in clinical trials, real‐world evidence is scarce. Patients and Methods: POSEIDON was a prospective non‐interventional study designed to evaluate effectiveness, safety and quality of life (QoL) of POM/DEX in patients with relapsed or refractory MM (R/RMM) pretreated with at least two prior therapy lines including both lenalidomide and bortezomib in real world in Germany. Patients received POM/DEX according to physicians' choice. Data were analyzed descriptively. Results: Between 2014 and 2017, 151 patients were enrolled, 144 patients with a median of three prior therapy lines qualified for effectiveness analysis. Median age was 73.2 years. Median progression‐free and overall survival were 6.3 months [95% confidence interval (CI) 5.2, 8.6] and 12.9 months [95% CI 10.6, 15.1]. Most frequent grade 3/4 adverse events were leukopenia (8.2%), pneumonia (7.5%) and anemia (5.5%). QoL was maintained after start of POM/DEX. Conclusion: The results of POSEIDON support the effectiveness and safety of POM/DEX in R/RMM patients pretreated with lenalidomide and bortezomib and highlight the clinical value of the POM/DEX regimen in the real‐world setting. Registered at clinicaltrials.gov (NCT02075996).